1998
DOI: 10.1021/jf980801+
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Residual Levels of Six Pesticides during Elaboration of Red Wines. Effect of Wine-Making Procedures in Their Dissappearance

Abstract: The effect of wine-making procedures on the concentrations of six pesticides (chlorpyrifos, penconazole, fenarimol, vinclozolin, metalaxyl, and mancozeb) in red wines has been studied. During maceration stage (4 days), the percentage remaining of chlorpyrifos, penconazole, and metalaxyl was approximately 90%, whereas that of fenarimol, vinclozolin, and mancozeb is somewhat smaller (74-67%). The residual levels found in pressed must were Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 9 publications
5
62
0
3
Order By: Relevance
“…The higher residue removal observed in red wine vinification is in part due to the malolactic fermentation, which reduced pesticide residue from 44 to 76%, particularly in the cases of tebuconazole and imidacloprid, respectively (Figure 2). This fact is in concordance with several studies that have shown the importance of the fermentation process in residue losses (Navarro et al, 1999;Cabras and Angioni, 2000;Fernandez et al, 2005;Gonzalez-Rodriguez et al, 2009). However, some of these authors did not found effect of malolactic fermentation on quinoxyfen, mepanipyrim, carbaryl, carbendazim, chlorothalonil, fenarimol, metalaxyl, oxadixyl, procymidone, triadimenol or tebuconazol losses (Cabras et al, 1999;GonzalezRodriguez et al, 2009).…”
Section: Pesticide Residues During the Vinification Processsupporting
confidence: 92%
See 3 more Smart Citations
“…The higher residue removal observed in red wine vinification is in part due to the malolactic fermentation, which reduced pesticide residue from 44 to 76%, particularly in the cases of tebuconazole and imidacloprid, respectively (Figure 2). This fact is in concordance with several studies that have shown the importance of the fermentation process in residue losses (Navarro et al, 1999;Cabras and Angioni, 2000;Fernandez et al, 2005;Gonzalez-Rodriguez et al, 2009). However, some of these authors did not found effect of malolactic fermentation on quinoxyfen, mepanipyrim, carbaryl, carbendazim, chlorothalonil, fenarimol, metalaxyl, oxadixyl, procymidone, triadimenol or tebuconazol losses (Cabras et al, 1999;GonzalezRodriguez et al, 2009).…”
Section: Pesticide Residues During the Vinification Processsupporting
confidence: 92%
“…Contrary results can be found in the literature regardless of filtration and clarification practices used, though results depend on the types of pesticides and matrix (Navarro et al, 1999;Fernandez et al, 2005;Oliva et al, 2007).…”
Section: Pesticide Residues During the Vinification Processmentioning
confidence: 79%
See 2 more Smart Citations
“…Although the correct use of phytosanitary products and treatments does not have adverse effects for public or environmental health, fungicide residues in grapes can pass through the winemaking process and are still present in the final product. Luckily, the winemaking process and the oenological steps carried out can contribute to their reduction de MeloAbreu et al, 2006;Ferna´ndez, Oliva, Barba, & Ca´mara, 2005;Gonza´lez-Rodrı´guez, Cancho-Grande, & SimalGa´ndara, 2009a, 2011Jime´nez, Bernal, del Nozal, Bernal, & Toribio, 2007;Navarro, Barba, Oliva, Navarro, & Pardo, 1999).…”
Section: Introductionmentioning
confidence: 99%